2008
DOI: 10.22164/isea.v2i2.32
|View full text |Cite
|
Sign up to set email alerts
|

Social and Environmental Disclosure in the Annual Reports of Jordanian Companies

Abstract: Recently, much attention has been devoted by researchers to study social and environmental disclosure among corporations. Most of the studies were conducted in developed countries, with only a handful being undertaken in developing countries. This study aims to investigate the extent of social and environmental disclosure in the annual reports of Jordanian companies and examine if the level of disclosure is influenced by size of firm, government ownership and industry. In particular, disclosure with regard to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 19 publications
3
53
0
1
Order By: Relevance
“…For example, Ismail and Ibrahim (2012) found that 85% of the Jordanian companies disclose some environmental information where the sample included 60 companies in the manufacturing and service sectors. As well, Bayoud et al (2012) found for annual reports 60% of companies from different sectors disclose four categories "employee disclosure; community involvement disclosure; consumer disclosure; environmental disclosure" of corporate social responsibility (CSR) whereas 5% of companies do not present CSR information in their annual reports.…”
Section: Petroleum Industry In Middle East and North Africa (Mena)mentioning
confidence: 99%
“…For example, Ismail and Ibrahim (2012) found that 85% of the Jordanian companies disclose some environmental information where the sample included 60 companies in the manufacturing and service sectors. As well, Bayoud et al (2012) found for annual reports 60% of companies from different sectors disclose four categories "employee disclosure; community involvement disclosure; consumer disclosure; environmental disclosure" of corporate social responsibility (CSR) whereas 5% of companies do not present CSR information in their annual reports.…”
Section: Petroleum Industry In Middle East and North Africa (Mena)mentioning
confidence: 99%
“…Moreover, large entities have adequate resources at their disposal to enable them collect, analyse and present huge data at a lower cost. Studies like those of Alsaeed, (2006), Ismail and Ibrahim (2008) and Dhar and Mitra (2010) have found size of the firm to be a good explaining factor of social and environmental reporting. It is therefore hypothesized that H 1 : There is a positive relationship between entity's size and the social and environmental disclosure.…”
Section: Entity's Sizementioning
confidence: 91%
“…These studies suggest that reporting of social and environmental disclosure has improved over the years in developed countries. Araya quoted by Ismail and Ibrahim (2008) reported that multinational companies from developed countries are leading when it comes to producing information on environmental disclosure. The author reported that for the period 1990 to 2003, 58% of all separate reports published around the world came from Europe, 20% came from America (which included US, Canada and Brazil) and 20% from Asia.…”
Section: Social and Environmental Disclosure In Developed Countriesmentioning
confidence: 99%
See 2 more Smart Citations